Anaerobic soil disinfestation for the management of soilborne pathogens: A review - Lopes, Everaldo Antônio; Canedo, Ellen Júnia; Gomes, Vanessa Alves [UNESP]; Vieira, Bruno Sérgio; Parreira, Douglas Ferreira; Neves, Wânia Santos (Elsevier, 2022)
Anaerobic soil disinfestation (ASD) is an ecological alternative to chemical soil fumigation. The method consists in incorporating easily decomposable organic materials into the soil, followed by irrigation to saturation and soil cover with impermeable plastic. Cereal brans, molasses, ethanol, and vegetable wastes are the main sources of carbon used in ASD. The soil remains covered from 3 to 10 weeks. Accumulation of toxic anaerobic decomposition products, antagonism by anaerobic organisms, lack of oxygen and the combination of all these factors are the main mechanisms of action of the technique against plant pathogens. Here, we reviewed the potential of ASD in the management of plant-pathogenic fungi, bacteria and nematodes.
Keywords: Biological soil disinfestation; Control of plant diseases; Reductive soil disinfestation; Soil-borne pathogens; Sustainable systems